Use of Agrobacterium rhizogenes Strain 18r12v and Paromomycin Selection for Transformation of Brachypodium distachyon and Brachypodium sylvaticum - Collier, Ray; Bragg, Jennifer; Hernandez, Bryan T.; Vogel, John P.; Thilmony, Roger (Frontiers in Plant Science, 2016)
The genetic transformation of monocot grasses is a resource intensive process, the quality and efficiency of which is dependent in part upon the method of DNA introduction, as well as the ability to effectively separate transformed from wildtype tissue. Agrobacterium-mediated transformation of Brachypodium has relied mainly on Agrobacterium tumefaciens strain AGL1. Currently the antibiotic hygromycin B has been the selective agent of choice for robust identification of transgenic calli in Brachypodium distachyon and Brachypodium sylvaticum but few other chemicals have been shown to work as well for selection of transgenic Brachypodium cells in tissue culture. This study demonstrates that Agrobacterium rhizogenes strain 18r12v and paromomycin selection can be successfully used for the efficient generation of transgenic B. distachyon and B. sylvaticum. Additionally we observed that the transformation rates were similar to or higher than those obtained with A. tumefaciens strain AGL1 and hygromycin selection. The A. rhizogenes strain 18r12v harboring the pARS1 binary vector and paromomycin selection is an effective means of generating transgenic Brachypodium plants. This novel approach will facilitate the transgenic complementation of T-DNA knockout mutants of B. distachyon which were created using hygromycin selection, as well as aid the implementation of more complex genome manipulation strategies which require multiple rounds of transformation.